PENGARUH PENGAWASAN TERHADAP KINERJA PEGAWAI PADA BADAN PERIJINAN DAN PENANAMAN MODAL DAERAH PROVINSI KALIMANTAN TIMUR DI SAMARINDA - Abdul Malik (Jurnal Administrasi Bisnis Fisipol Unmul, 2020)
The purpose of this study was to determine the effect of supervision on employee performance at the Regional Licensing and Investment Board (BPPMD) of East Kalimantan Province in Samarinda. This research was conducted using a simple regression analysis tool to find the regression equation. Then to see the level of influence used Pearson product moment correlation coefficient. Then to determine the size of the contribution or influence is used next formula determinant coefficient for hypothesis testing is done by comparing the value of rcount with the value of rtable. The results of this study produce the following equations and values. Obtained a regression equation Ŷ = 2.084 + 0.582 X. And the value of the correlation coefficient (r) of 0.463 and the determinant coefficient of 21.4% of supervision affects the performance of BPPMD employees. In the hypothesis test produces a comparison that is rcount of 0.463> rtable (attached) of 0.297 with a significance level of 5%, so it can be concluded that the working hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected which means that supervision affects the performance of BPPMD employees East Kalimantan Province in Samarinda. Based on this research, it is suggested to improve employee performance by providing training that is ongoing and increasing supervision is carried out in stages.